Growth and yield quality of organic spinach (Amaranthus spp.) in response to different nitrogen fertilizer sources and rates - Manaf, Faridah (2020)
The use of different organic nitrogen (N) fertilizers were found to give different results in terms of soil fertility, growth and nutrient content of plants. A test by [1] on onions planted on a growth media mix treated with amino acid significantly had (p <0.05) the highest Ca, N and leaf chlorophyll contents. As well as significantly (p <0.05) increased anthocyanin content, the overall plant growth was improved by the amino acid treatment. As reported by [2], positive improvement was observed on acidic soils treated with biochar in the form of a significant corn crop yield effect. Therefore, to study the effect of different inputs of nitrogen on organic leafy vegetables, a greenhouse experiment was conducted on spinach to compare the effect of different treatments of organic N (% of organic N), namely T1: 0% N (Control without any fertilizer), T2: 2% N (Current practice control with 2% N from biochar), T3: 4% N (2% N from biochar + 2% N from fish amino acid/FAA), and T4: 6% N (2% N from biochar + 4% N from FAA) on soil chemical properties, plant physiology and plant phytochemical content (antioxidant, total phenolic and flavonoid content). The research trials were carried out at the integrated organic farming, MARDI Serdang in two cycles. Treatments were applied 14 days after seeding (DAS) at a uniform rate of 8 g/pot (equivalent to 2 t/ha). The results obtained revealed that treatment with T3 (2% N from biochar + 2% N from FAA) had significantly (P < 0.05) improved the soil CEC, C, available-P and exchangeable-Ca. Meanwhile, the soil pH was found to remain stable from the initial seeding (0-day) until the harvesting day (35-DAS) under the current practice using 2% N from biochar (T2). Improved nitrogen uptake by spinach was also observed under T3. The plant height and fresh weight of spinach differed significantly (P < 0.05) under T3. Spinach analysed using the 2,2-diphenyl-1-picrylhydrazyl-hydrate (DPPH) statistically showed that the treatment with 4% N (T3) was found to have significantly (P < 0.05) the highest activity of antioxidant with 61.89 mg AA/ DW g per sample compared to spinach grown under both control treatments and 6% N input (T4). These findings bring to the conclusion that 4% of N ii from organic sources has been identified as an effective amount to improve the antioxidant activity of spinach, other similar leafy vegetables, farmed under the organic system with no significant loss in plant growth and yield. The way forward for this research is to expand the investigation on the other sources of organic materials and to measure the mineralized nitrogen and other secondary metabolites to strengthen the finding and potential benefits, especially for our local organic agriculture.